Prevalence of antibiotic-resistant bacteria amongst dogs in Africa: A meta-analysis review - Yaovi, Ayaovi B.; Sessou, Philippe; Tonouhewa, Aretas B.N.; Hounmanou, Gildas Y.M.; Thomson, Deborah; Pellé, Roger; Farougou, Souaïbou; Mitra, Arindam (AOSIS, 2022)
Antimicrobial resistance (AMR) is a global public health threat for both human and veterinary medicine. Increasing evidence suggests that animals are important sources of AMR to humans; however, most of these studies focus on production animals. In order to determine the pattern of AMR in pets, mainly in dogs in Africa, a meta-analysis was performed with AMR studies conducted in African countries and published between January 2000 and January 2021 in four databases: Medline (PubMed), Scopus, Cab abstract and Google Scholar. Seven bacterial strains, namely Staphylococcus aureus, Escherichia coli, Salmonella spp., Pseudomonas aeruginosa, Streptococcus pyogenes, coagulase-negative Staphylococcus (SNC) and Staphylococcus pseudintermedius were included in this study. A total of 18 out of 234 indexed articles met the study criteria. The results revealed that multiple bacteria were resistant to various commonly used antibiotics including enrofloxacin, ciprofloxacin, gentamicin, amoxicillin, clavulanic acid, cotrimoxazole, streptomycin, tetracycline and chloramphenicol. Concerning multidrug resistance, E. coli strains came first with the highest prevalence of 98%, followed by P. aeroginosa (92%) and Salmonella spp. (53%). In contrast, the overall prevalence of multidrug resistance was low for S. aureus (18%) and S. pseudintermedius (25%). It is therefore urgent to find, as soon as possible, alternatives to replace these antibiotics, which have become ineffective in controlling these bacteria in dogs in Africa. Moreover, further metagenomic studies are needed to describe the full resistome and mobilome in dogs regardless of the bacteria.